Analysis of state administrative court procedural law: A recent review and its practical implications - Sutrisno, Anom (Indonesian Journal of Multidisciplinary Science, 2024)
In Indonesia, the Administrative Court Procedure (ATUN) is a vital law enforcement tool that resolves disputes between government and citizens or between government agencies. This article aims to provide in-depth insight into the dynamics of ATUN, as well as explore its practical implications in the context of state administration law enforcement in Indonesia. The research method utilized is normative juridical as the main approach to analyzing and evaluating the legal framework governing ATUN. The next step is to identify problems that arise in ATUN and analyze the applicable legal norms, both regulations and court decisions, and draw conclusions and practical implications from these findings. The results show that ATUN has undergone changes that have a positive impact on strengthening the enforcement of justice in the State Administrative Court field. With the adoption of technology, the speed, accuracy, and reliability in handling administrative cases has improved significantly. Finally, mediation has also become a more efficient alternative in resolving disputes, providing faster solutions and more affordable costs compared to conventional judicial processes.